Jurisprudence Conditioning of Defense Law No (13) of 1992 in the Hashemite Kingdom of Jordan - Alamro, Iman Madallah Althbeitat (Arab Journal for Sciences and Research Publishing, 2022)
This scientific study aimed to clarify the legal principles that can be relied upon in enacting exceptional laws restricting the movement of individuals in light of the Corona pandemic, in addition to the need to clarify the purpose of the Jordanian Defense Law, and the extent to which it is consistent with the overall jurisprudence rules, then to show the great impact of preserving the purposes of Sharia through The enactment of laws in some calamities related to the Corona pandemic. The previous studies, despite the importance of what they included, did not address the issue of exceptional laws imposed by states on their citizens, including the Jordanian Defense Law at the beginning of the pandemic, and therefore the efforts in previous research do not dispense with conducting the current study, and it is not a repetition of previous studies, but rather a continuation In addition to the findings of previous studies, deepening those studies and clarifying many of the provisions contained in previous studies, Finally, the current study is characterized by showing the flexibility of Islamic jurisprudence and its ability to absorb developments and exceptional rulings, and then legitimate rooting for that, and shed light on the rulings for this pandemic from the perspective of legitimate politics, with mentioning the sayings on the issue, and a statement of those who said it from the people of knowledge, and the presentation of the dispute is according to Fiqh schools, and if there is nothing on the matter except the sayings of contemporary jurists, then the researcher arranges the sayings, beginning with the saying of the most, Then confine yourself to the reputable schools of jurisprudence, taking care to mention what is easy to understand from the sayings of the righteous predecessors that can be used in the matter, with attention to the sayings of respected contemporary scholars, the collective ijtihad councils, the decisions and recommendations of the Islamic Fiqh Academy, and the sayings of researchers in the matter, evidence, texts, fundamental rules and fatwas Jurisprudence institutions and complexes in these developments in comparison with the sayings of the forerunners and later scholars and the presentation of evidence, results and recommendations resulting from this study.